Termination Of Employment Due To the Global Manufacturing Crisis: A Comparative Study of Worker Protection in Indonesia, Germany, and Vietnam - Lalu Hadi Adha; Yazid Fathoni; Diangsa Wagian (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study aims to analyze the driving factors of the global manufacturing crisis and evaluate the legal protection frameworks for workers facing mass layoffs in Indonesia, Germany, and Vietnam. It explores how each nation adapts its national regulations to mitigate the socio-economic impacts of geopolitical instability and the global economic slowdown. Using a juridical-normative method with a comparative approach, the analysis is conducted through a legal-dogmatic lens, processing materials through technical, teleological, and external systematization levels.The study finds that although the manufacturing crisis is a shared global phenomenon, protective responses vary significantly. Indonesia relies on the Job Creation Law and the Job Loss Guarantee (JKP) social safety net. Germany emphasizes "socially justified" dismissals and the Kurzarbeit (short-time work) scheme to prioritize job retention. Meanwhile, Vietnam is modernizing its legal framework through the 2025 Employment Law, focusing on vocational retraining and a multi-pillar social insurance system. Legal protection must evolve from mere financial compensation toward a tripartite synergy between the government, employers, and labor unions. Effective protection requires a balance between labor market flexibility and robust social safety nets to ensure that termination is a last resort and that affected workers remain competitive in a shifting global economy.